Amamentação na percepção das mães nos primeiros seis meses de vida - Moraes, Gécica Gracieli Wust de (2019)
In Brazil, the predominance of exclusive breastfeeding (BF) is less than 50%, thus being necessary to encourage mothers to increase the duration of this practice. Therefore, it is essential to reveal the facets that can interfere in the promotion of exclusive BF, as in the self-confidence for breastfeeding (BF). For this purpose, the health professional must know how the woman feels about the breastfeeding management. Accordingly, the objective was to identify the maternal perception related to their confidence in breastfeeding. Qualitative and quantitative study of a prospective cohort developed with women who had their children in the period from July to October of 2017, in a university hospital in the West of Paraná State. These women were followed up until the sixth month after the maternity discharge. The data collection happened in two stages: in the first, the quantitative stage, which happened right after the baby’s birth, between 24 and 48 hours after the delivery, a sociodemographic data form and the self-efficacy scale for BF were applied to 158 women; in the following, up to six months after the delivery, the follow-up was done by telephone contact, in order to maintain ties with the participant, in the first and third month, and by a home visit in the sixth month, when the self-efficacy scale was reapplied to 128 participants. In the second stage, in the qualitative stage, 22 women were selected by lot to participate in the in-depth interview. Quantitative data were analyzed by statistical treatment and the qualitative data were analyzed using thematic content analysis. Most of the puerperal women met the following characteristics: were married/stable union (89.24%), white people (82.9%), aged between 18 and 25 years old (46.20%) and family income of one to two minimum wages (36.07%), had finished high school (38.6%), had vaginal delivery (51.2%), had breastfed previously (60%) and kept the exclusive BF in the sixth month (45.3%). The self-efficacy scale for BF showed high internal consistency (α= 0.9481), providing that the majority women presented high efficacy for BF since their babies’ birth. A statistically significant association was evidenced by the logistic regression between exclusive BF and high score in the self-efficacy scale questions regarding the use of infant formula as a supplement and breast exchange in the same feeding (X2 = 1.374). Exclusive BF was significantly associated with the presence of a partner up to the sixth month (p = 0.043), considering that the partner does not work out (p = 0.020), and with a family income of up to a minimum wage (p = 0.044). The thematic categories refer to the material perception about the act of breastfeeding, breastfeeding confidence and to the experiences with breastfeeding up to the sixth month. The self-efficacy scale for breastfeeding has proven to be a valid and reliable measure of maternal confidence in breastfeeding, which may help health professionals precociously diagnose preterm puerperal women at risk of early weaning. Thus, they can help them improve their self-efficacy and, consequently, contribute to improving the prevalence of exclusive BF. However, when the nursing mothers were given voice, it was observed that the association between qualitative and quantitative data allowed aspects that the scale does not size to be identified, comprehending that only the scores related to maternal confidence to breastfeed the child are not sufficient to promote the exclusive BF. Therefore, the association of the referred scale to the full-time and individual care of these puerperal women will allow a broad breastfeeding approach management by the health professionals.